Metal−Organic Frameworks for Liquid Phase Applications - Nalaparaju, Anjaiah (Adv Sci (Weinh), 2021)
In the last two decades, metal−organic frameworks (MOFs) have attracted overwhelming attention. With readily tunable structures and functionalities, MOFs offer an unprecedentedly vast degree of design flexibility from enormous number of inorganic and organic building blocks or via postsynthetic modification to produce functional nanoporous materials. A large extent of experimental and computational studies of MOFs have been focused on gas phase applications, particularly the storage of low‐carbon footprint energy carriers and the separation of CO(2)‐containing gas mixtures. With progressive success in the synthesis of water‐ and solvent‐resistant MOFs over the past several years, the increasingly active exploration of MOFs has been witnessed for widespread liquid phase applications such as liquid fuel purification, aromatics separation, water treatment, solvent recovery, chemical sensing, chiral separation, drug delivery, biomolecule encapsulation and separation. At this juncture, the recent experimental and computational studies are summarized herein for these multifaceted liquid phase applications to demonstrate the rapid advance in this burgeoning field. The challenges and opportunities moving from laboratory scale towards practical applications are discussed.